Sámi Research in Transition : Knowledge, Politics and Social Change - Junka-Aikio, Laura (Taylor & Francis, 2021)
For several decades now, there have been calls to decolonize research on the Indigenous Sámi people, and to make it accountable to the Sámi society. While this has contributed to the rise of a vibrant Sámi research community in the Nordic countries, less attention has been paid to what extent, and how the "Sámi turn" in research has been implemented in practice. Written by prominent Nordic and Sámi scholars anchored in the Sámi research communities in Finland, Norway and Sweden, this volume explores not only the meanings and implications of this turn across disciplines, but also some of the challenges that efforts to create space for Sámi voices, knowledges and perspectives still meet today. The book provides a timely, interdisciplinary engagement with the central themes that have framed the development of Sámi research, and a critical appraisal of the impact that efforts to decolonize research in the Sámi context have had upon Nordic societies and state policies so far. Sámi Research in Transition is valuable for scholars and students interested in Sámi history and society, Arctic and Circumpolar Indigenous studies and critical studies on the relationship between knowledge and social change. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.